Novel oral glucose‐lowering drugs are associated with lower risk of all‐cause mortality, cardiovascular events and severe hypoglycaemia compared with insulin in patients with type 2 diabetes. Issue 6 (16th March 2017) - Nyström, Thomas; Bodegard, Johan; Nathanson, David; Thuresson, Marcus; Norhammar, Anna; Eriksson, Jan W.
Abstract : Aims: To investigate the association of novel oral glucose‐lowering drugs (GLDs), compared with that of insulin, with risk of all‐cause mortality, cardiovascular disease (CVD) and severe hypoglycaemia. Methods: During 2013 to 2014 all patients with type 2 diabetes in Sweden identified as new users of novel oral GLDs, either dipeptidyl peptidase‐4 (DPP‐4) inhibitors or sodium‐glucose cotransporter‐2 (SGLT2) inhibitors (only dapagliflozin available in Sweden during the study period), with those initiating insulin as a comparison group, in the Prescribed Drug Register were included and followed in the Patient and Cause of Death Registers. The novel GLD group and insulin group were matched 1:1 using propensity score. Cox regression models were used to estimate risks. Results: Of 37 603 patients, 21 758 were matched 1:1 to novel GLD vs insulin groups, with median follow‐up times of 1.51 years (16 304 patient‐years) and 1.53 years (16 306 patient‐years), respectively. Treatment with novel GLDs was associated with a 44% (hazard ratio [HR] 0.56 [95% confidence interval CI 0.49‐0.64]), 15% (HR 0.85 [95% CI 0.73‐0.99]) and 74% (0.26 [95% CI 0.12‐0.57]) lower risk of all‐cause mortality, CVD and hypoglycaemia, respectively, compared with insulin treatment. In separate analyses for the two novel GLDs, dapagliflozin was associated with lower risks of all‐cause mortality and CVD (56% [HR 0.44, 95% CI 0.28‐0.70] and 49% [HR 0.51, 95% CI 0.30‐0.86], respectively), while DPP‐4 inhibitor treatment was associated with lower risk of all‐cause mortality (41% [HR 0.59, 95% CI 0.51‐0.67]), but not with CVD (HR 0.87, 95% CI 0.75‐1.01). Conclusions: Novel oral GLD treatment was associated with lower risk of all‐cause mortality, CVD and severe hypoglycaemia compared with insulin treatment. Dapagliflozin was associated with a lower risk of both all‐cause mortality and CVD, whereas DPP‐4 inhibitor treatment was only associated with lower risk of all‐cause mortality.